Calcination Effects and Photocatalytic Activity of Porous SiO2-TiO2 Material - Wang, Hong; Han, Xiaofang; Zhang, Wenjie; Li, Ruyuan (Asian Journal of Chemistry, 2014)
A porous SiO2-TiO2 photocatalyst was prepared through co-sol-gel method using PEG1000 template for photocatalytic degradation of methyl orange. Photocatalytic degradation was conducted after adsorption equilibrium to identify the contribution of both adsorption and photocatalytic degradation. The optimum calcination condition for the porous SiO2-TiO2 is 500 °C for 3 h. The adsorption of methyl orange on the photocatalyst has no apparent change in the whole temperature range. Nearly 96.5 % of the initial methyl orange is removed in 100 min under UV light irradiation with the existence of the porous SiO2-TiO2. Methyl orange degradation follows the first order kinetics equation. The azo and benzene structure are degraded into small molecules during photocatalytic oxidation process.